Bone damage and health-related quality of life in Hodgkin lymphoma survivors: closing the gaps - Mancuso, Salvatrice; Mattana, Marta; Giammancheri, Federica; Russello, Federica; Carlisi, Melania; Santoro, Marco; Siragusa, Sergio (Frontiers in Oncology, 2024)
In the recent decades, remarkable successes have been recorded in the treatment of Hodgkin's lymphoma to the point that today it represents one of the neoplasms with the highest rates of cure and with the highest life expectancy. Nonetheless, this raises the concern for the health of long-term survivors. Late side effects of treatments in synergy with other risk factors expose survivors to increased morbidity and impaired quality of life. In the complexity of the topics concerning these last aspects, an area of growing interest is that of bone damage that follows Hodgkin Lymphoma and its treatments. In this narrative review, we conducted our work through assessment of available evidence focusing on several aspects linking bone damage and quality of life with Hodgkin lymphoma and its treatments. At present, the problem of osteopenia and osteoporosis in Hodgkin lymphoma survivors is a theme for which awareness and knowledge need to be implemented.